Transforming Ethiopian food systems: Leveraging private sector incentives to drive agroecological wheat production - Balcha, Yodit; Tibebe, Degefie; Ebrahim, Mohammed; Filippi, Viviane; Mockshell, Jonathan (2024)
In recent years, Ethiopia has embarked on transforming the country's food system through different regulations and policies to achieve food security for its citizens. Its 'Cluster-based Agricultural Commercialization Strategy (CACS)' comes to one's mind when talking about policies to transform smallholder agriculture into a more commercially oriented and market-driven sector. Although the CACS has provided valuable contribution in organizing and supporting farmers through cluster-based approaches to increase economies of scale, improving access to inputs, markets, finance, and technology, to enhancing value chain integration and competitiveness, and moving towards achieving the Sustainable Development Goals (SDGs), the Paris Agreement, and biodiversity targets, there is a need to provide incentives and invest in agroecological practices that are sustainable, inclusive, and resilient.